Child-Mother Index: a new risk factor for selected adverse maternal birth outcomesAJOG Global Reports at a Glance - Mohammed Rohi Khalil, MD, PhD; Rikke Guldberg, MD; Bente Mertz Nørgård, MD, PhD; Niels Uldbjerg, MD, DMSc; Sonja Wehberg, MD, PhD (Elsevier, 2022)
BACKGROUND: Over decades, obstetricians have evaluated a range of risk factors to improve the prediction of adverse birth outcomes. OBJECTIVE: This study aimed to assess the effectiveness of the Child-Mother Index as a risk factor indicator for selected adverse maternal birth outcomes. STUDY DESIGN: We assessed the Child-Mother Index by multinomial regression models using register-based data containing all singleton births in Denmark in 2009 with a gestational age between 37+0 and 41+6 weeks. The Child-Mother Index is defined as the weight of the newborn divided by the squared maternal height. RESULTS: Data from 47,007 births were included. Both the Child-Mother Index mean and Child-Mother Index median were 12.6 hg/m2 (range, 4.8-22.4). In the multivariable model, the relative risk ratios for Child-Mother Index above 14.1 hg/m2 were 2.2 (95% confidence interval, 1.6-3.1) for third- and fourth-degree perineal tears, 2.0 (1.6-2.5) for nonelective cesarean delivery, and 1.0 (0.8-1.3) for instrumental procedures. Equivalent figures for a Child-Mother Index below 11.2 hg/m2 were 0.6 (0.4-1.0), 1.0 (0.8-1.2), and 0.7 (0.6-0.9), respectively.By comparing a multivariable model with the Child-Mother Index included with a model without the Child-Mother Index included using a likelihood ratio test, a statistically significant difference was found in favor of the Child-Mother Index inclusion (P<.001). CONCLUSION: The Child-Mother Index constitutes a potential useful risk factor indicator for statistical analyses on data after birth. The value of the Child-Mother Index based on the estimated fetal weight before birth deserves evaluation.